Analisis Beban Kerja untuk Menentukan Kebutuhan Tenaga Kerja Optimal pada Proses Produksi Kemasan Karton - Alim Mulya Wibowo; Erni Puspanantasari Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT. XYZ is a manufacturing company that operates in the production industry cardboard packaging. In its operations, the company often fails to meet its production target of 285,000 units per month. The current workforce allocation policy, which evenly distributes 15 workers across 5 work stations (3 operators each), is indicated as the cause of an imbalance in operational workloads. This study aims to mathematically analyze workloads to determine the optimal workforce requirements using the Full-Time Equivalent (FTE) method. The research process began with a time study to determine standard times for each workstation. The standard times and production targets were then used to calculate FTE indices, which classified workloads into underload, normal, or overload categories. Based on the analysis results, it was found that the sewing station was overloaded with an FTE index of 3.72, which caused a bottleneck, while the other four stations were underloaded. Through the proposed improvement to the FTE-based workforce allocation, the company actually only needs a total of 10 workers, broken down as follows: 1 person at the cutting station, 2 in printing, 2 in punching, 4 in sewing, and 1 in finishing. Implementing this proposal not only results in an efficiency gain of 5 employees but has also been shown to increase maximum production capacity from 229,894 units to 306,526 units per month, thereby enabling the company to meet its order fulfillment targets without requiring additional overtime hours.